EKSISTENSI WILAYATUL HISBAH DALAM SISTEM PEMERINTAHAN ISLAM - Marah Halim (Islam Futura, 2011)
This study tries to elaborate existense of Wilayatul Hisbah in Islamic governance system since the Prophet period to date. Description about it obtained from studying the process chrystalization of hisbah by Classic Islam scholars and its institutionalization in Islamic governance system. By using historic-descriptive approach to the existing bibliographical data, obtained a onclusion that hisbah "do not be eliminated" from Islamic governance because it represents the personification of Islamic ethic itself. Along with decrease of Islami influence, the concept also decreased.